Penerapan Personal Selling PT.PGN Area Bekasi Dalam Menarik Minat Beli Pelanggan Rumah Tangga - Abdul Aziz Pamungkas; Jamiati KN (STIKes Ibnu Sina Ajibarang, 2024)
In the world of marketing, the high level of marketing of diverse products is a problem or challenge for the marketing division in every company in terms of market competition. The research entitled